Synthesis of Edible Film from Crab Shell Chitosan and Banana Peel Starch - Santi, Sintha Soraya; Hariyanto, Ayu Puspita Kandhi; Hartono, Muhamad Dendy (Nusantara Science and Technology Proceedings)
Nowadays the use of plastics has become an important material so that the demand for home products as well as in industrial production is increasing. The activity of using plastics is increasing, causing complex environmental problems because it’s non-biodegradable. One of the biodegradable plastics is an edible film, which is a thin layer as a food packaging or coating which can be consumed together with the packaged product. In this research, the edible film was made using a synthesis method with raw materials such as crab shell chitosan, banana peel starch, and glycerol. Chitosan effects film reinforcement, starch functions as a film matrix former and glycerol also functions to increase the flexibility of the film. Through this research, it is hoped that the ratio of raw materials for the edible film including starch, chitosan, and glycerol can affect the characteristics of edible film such as tensile strength, percent elongation, percent of the solubility value in water.